Effectiveness of DIR/Floortime Intervention on Communication Skills Development in Elementary School Students with Autism Spectrum Disorder - Dwidjantoro, Muhammad Irma Sunu; Sukinah, Sukinah (Papanda Publisher, 2025)
Communication impairments represent core challenges in children with Autism Spectrum Disorder (ASD), significantly impacting academic and social functioning. The Developmental, Individual-differences, Relationship-based (DIR)/Floortime intervention shows promise for addressing these deficits, yet limited research has examined its effectiveness in elementary school settings. This study employed a single-subject research design with A-B-A' reversal methodology to examine DIR/Floortime intervention effects on communication skills in a 10-year-old male student with ASD. The participant was enrolled in fourth grade at an elementary school in Telen District. Data collection utilized direct behavioral observation and performance-based assessment across three phases: baseline 1 (4 sessions), intervention (6 sessions), and baseline 2 (4 sessions). The DIR/Floortime protocol followed established five-phase procedures including observation, opening communication circles, following the child's lead, expanding interactions, and natural closure. Data analysis employed within-condition and between-condition analyses, including trend analysis, stability assessment, and data overlap calculations. Systematic improvements were observed across intervention phases. Mean scores increased from 29.72 in baseline 1 to 77.1 during intervention, with maintenance at 93.8 in baseline 2, representing a 215% improvement from initial baseline. Between-condition analysis revealed 0% data overlap across phase transitions, indicating exceptionally strong intervention effects. Within-condition analysis showed 100% stability in baseline 2, confirming sustained skill acquisition. The findings provide robust evidence for DIR/Floortime effectiveness in elementary school settings. Results extend previous research by demonstrating successful implementation in educational environments, supporting cost-effective, relationship-based interventions that promote lasting communication improvements. The 0% data overlap establishes clear functional relationships between DIR/Floortime and communication skill development, aligning with systematic reviews supporting DIR/Floortime as an evidence-based practice for children with ASD.